Cross feeding of glucose metabolism byproducts of Escherichia coli human gut isolates and probiotic strains affect survival of Vibrio cholerae. Issue 1 (December 2017) - Sengupta, Chirantana; Ekka, Manjula; Arora, Saurabh; Dhaware, Prashant; Chowdhury, Rukhsana; Raychaudhuri, Saumya
Abstract Vibrio cholerae converts glucose into either acid or the neutral end product acetoin and its survival in carbohydrate enriched media is linked to the nature of the byproducts produced. It has been demonstrated in this study thatEscherichia coli strain isolated from the gut of healthy human volunteers and the commonly used probioticE. coli Nissle strain that metabolize glucose to acidic byproducts drastically reduce the survival ofV. cholerae strains irrespective of their glucose sensitivity and acetoin production status. Accordingly, E. coli glucose transport mutants that produce lower amounts of acidic metabolites had little effect on the survival ofV. cholerae in cocultures. Thus, cross feeding of byproducts of glucose metabolism by heterologous bacteria modulates the survival ofV. cholerae in glucose rich medium suggesting that composition of the gut microbiota could influence the outcome ofV. cholerae infection especially when glucose based ORS is administered.